A sensitive electrochemical sensor based on wrinkled mesoporous carbon nanomaterials for rapid and reliable assay of 17β-estradiol. (10th March 2022) - Xie, Peng; Liu, Zhenping; Huang, Shuqing; Chen, Jiamei; Yan, Yu; Li, Na; Zhang, Minmin; Jin, Mingliang; Shui, Lingling
Highlights: A wrinkled mesoporous carbon nanomaterial with hollow nanocage-like structure was synthesized. A reusable electrochemical sensor was constructed for sensitive and reliable assay of 17β-estradiol. The constructed sensor was successfully applied for determining 17β-estradiol in milk and river water samples. Abstract: In this study, we establish a sensitive and reusable electrochemical sensor for assay of 17β-estradiol (17β-E2) based on wrinkled mesoporous carbon ( w MC) nanomaterials. w MC was synthesized by using the wrinkled silicon nanoparticle ( w SiO2 NP) as supporting and sacrificial hard template, which formed a hollow nanocage-like structure. Such a carbon-based composite structure endows rich accessible active sites, large specific surface area and high electrocatalytic activity. High performance electrochemical sensor based on the w MC modified electrodes has been achieved for various assays, presenting excellent reusability by a simple regeneration treatment for removal of fouling (phenolic compounds) in tetrabutyl ammonium hexafluorate (TAH)-acetone solution. For 17β-E2 assay, the linear response in the ranges of 0.05–10.0 μM and 10.0–80.0 μM have been achieved with the detection limit of 8.3 nM (S/ N  = 3). This sensor has also been successfully applied for the determination of 17β-E2 in the milk and real water samples, exhibiting comparable results measured using a high-performance liquid chromatography. This sensor presents high sensitivity, selectivity, reproducibility, and especially the validated recoverability, showing high potential for endocrine disrupting chemical assay. Graphical abstract: A sensitive and reusable electrochemical sensor based on wrinkled mesoporous carbon ( w MC) nanomaterial was constructed for detecting 17β-estradiol in milk and river water samples. Image, graphical abstract